Predictors of Clinically Significant Postoperative Events after Open Craniosynostosis Surgery. (May 2015) - Goobie, Susan M.; Zurakowski, David; Proctor, Mark R.; Meara, John G.; Meier, Petra M.; Young, Vanessa J.; Rogers, Gary F.
Abstract : Background: Craniosynostosis surgery is associated with clinically significant postoperative events requiring intensive care unit (ICU) admission. The authors investigate specific variables, which might influence the risk for these events, and thereby make recommendations regarding the need for postoperative ICU admission. Methods: A retrospective review of 225 children undergoing open craniosynostosis repair at a single center during a 10-yr period is reported. The primary outcome measure was the incidence of predefined clinically relevant postoperative cardiorespiratory and hematological events requiring ICU admission. Results: The incidences of postoperative cardiorespiratory and hematological events requiring ICU care were 14.7% (95% CI, 10.5 to 20.1%) and 29.7% (95% CI, 24.0 to 36.3%), respectively. Independent predictors of cardiorespiratory events were body weight less than 10 kg, American Society of Anesthesiologists physical status 3 or 4, intraoperative transfusion of greater than 60 ml/kg packed erythrocytes, and the occurrence of an intraoperative complication. The independent predictors of hematological events were body weight less than 10 kg, American Society of Anesthesiologists physical status 3 or 4, intraoperative transfusion of greater than 60 ml/kg packed erythrocytes, transfusion of hemostatic products (fresh-frozen plasma, platelets, and/or cryoprecipitate), and tranexamic acid not administered. Conclusions: Children undergoing craniosynostosis surgery are at increased risk for clinically significant postoperative events requiring ICU admission if they are less than 10 kg body weight, American Society of Anesthesiologists physical status 3 or 4, require intraoperative transfusion of greater than 60 ml/kg of packed erythrocytes, receive hemostatic blood products, or if they develop a significant intraoperative complication. Tranexamic acid administration was associated with fewer postoperative events. A predictive clinical algorithm for pediatric patients having major craniosynostosis surgery was developed and validated to risk stratify these patients. Abstract : Children undergoing craniosynostosis surgery are at increased risk for clinically significant postoperative events requiring intensive care unit admission if they are less than 10 kg body weight, American Society of Anesthesiologists physical status 3 or 4, require intraoperative transfusion of greater than 60 ml/kg of packed erythrocytes, receive hemostatic blood products, or if they develop a significant intraoperative complication.Supplemental Digital Content is available in the text.